Visual Functions Generating Conscious Seeing - Lamme, Victor A. F. (Frontiers in Psychology, 2020)
Visual functions are reviewed that coincide with conscious as opposed to unconscious vision. Four stages of vision are identified, going from the fully invisible, to subjectively invisible, unattended and clearly visible. It is proposed that feature extraction, categorization and some aspects of visual inference occur during full and subjective invisibility. Functions related to perceptual organization, such as grouping and figure-ground segregation occur during inattention as well as full visibility. It is argued that perceptual organization is the function that is central to understanding the transition from unconscious to conscious seeing. It is discussed what this implies for theories of consciousness such as Recurrent Processing Theory, Higher Order Thought Theory, Integrated Information Theory and Global Neuronal Workspace Theory.